Decreasing Incomes Increase Selfishness - Nickolas Gagnon; Riccardo D. Saulle; Henrik W. Zaunbrecher (Fondazione Eni Enrico Mattei (FEEM), 2021)
We use a controlled laboratory experiment to study the causal impact of income decreases within a time period on redistribution decisions at the end of that period, in an environment where we keep fixed the sum of incomes over the period. First, we inves-tigate the effect of a negative income trend (intra-personal decrease), which means a decreasing income compared to one's recent past. Second, we investigate the effect of a negative income trend relative to the income trend of another person (inter-personal decrease). If intra-personal or inter-personal decreases create dissatisfaction for an individual, that person may become more selfish to obtain compensation. We formal-ize both effects in a multi-period model augmenting a standard model of inequality aversion. Overall, conditional on exhibiting sufficiently-strong social preferences, we find that individuals indeed behave more selfishly when they experience decreasing incomes. While many studies examine the effect of income inequality on redistribution decisions, we delve into the history behind one's income to isolate the effect of income changes.
Keywords: C91; D31; D63; 330; Income Inequality; Income Change; Social Preferences; Social Comparison; Income Redistribution